The Implementation of Indonesian Sustainable Palm Oil on Oil Palm Plantations Smallholders in Kumai District, Central Kalimantan Province - Holpu Ronal Ambarita; Any Suryantini; Dwidjono Hadi Darwanto (Agro Ekonomi, 2023)
Indonesia Sustainable Palm Oil is one of responses of the Indonesian government’s responses to environmental issues, such as deforestation, and forest degradation. Central Kalimantan is a province in Borneo Island with the largest oil palm plantations, and it’s total area  is about 1.6 million ha, of which smallholder's plantation are covering an area of 166,000 hectares. There are many constraints faced by smallholder plantations to implement ISPO certification. Because of that, it is important to study the level of application of the ISPO criteria and, the factors that influence the implementation of ISPO in Kumai District, Central Kalimantan. The study used non-probability sampling with a total of 100 respondents. This research used descriptive analysis and the Gutman scale to determine the application of ISPO criteria, multiple linear regression analysis was used to determine the factors that influence the application of ISPO. The results of the analysis showed that (1) On average, smallholders implement 80% of ISPO criteria, and (2) ISPO criteria implemented by smallholders were influenced by the length of farming experience, education level, and the number of household’s members.